Implementasi Standar Akuntansi Keuangan EMKM pada UMKM Asglow Kartiasa Sambas - Novi Sentiya; Gustianti Gustianti (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
ASGLOW is a micro business run by Akhmad Wardiansyah since December 15 2020. The product being marketed is a saffron face mist. The purpose of this study is to determine the application of financial preparation reports based on SAK EMKM. The type of approach used is the quantitative method. Based on the results of the interviews, it is known that the business owner does not keep records in accordance with SAK EMKM. The process of preparing financial reports for MSME ASGLOW, business owners use the Microsoft Excel G application because it is easy to use in managing numbers. The research conducted on ASGLOW SMEs can be seen from the financial position of ASGLOW SMEs, namely assets Rp. 5,857,900.00, liabilities (liabilities) Rp. -, equity (capital) Rp. 5,857,900.00, net profit Rp. 1,167,875 ,00. With this research, it is hoped that business owners will pay more attention to recording financial reports in accordance with applicable standards.